ANALYSIS OF FLAME RETARDANT POLYPROPYLENE FOR PLASTIC INJECTION MOLDING USING BROMINATED AROMATIC COMPOUND - Muhammad Yusuf Nurfani; Dwi Arif Santoso (International Journal Science and Technology, 2022)
Flame Retardant (FR) is a type of thermoplastic material that is resistant to fire. Application of FR on various types of plastic resins such as polypropylene (PP), Acrylonitrile butadiene styrene (ABS), and other types of plastic resins. This study discusses the analysis of Brominated Aromatic Compound as a mixture of Polypropylene to produce PP-FR types for plastic injection molding with the material formulation method to perform a flame retardant test on the results of the specimens that have been made. This study shows that PP material and Acrylonitrile butadiene styrene can bind scanning microscopes with ×15,000 and ×30,000 zoom. The extrusion process results did not experience cracks after going through a chamber test of -5 ◦C to 70 ◦C for 120 hours on the specimen. In addition, the results of the flame retardant test fire can die in under 2 seconds